Anaesthetic efficacy and postinduction hypotension with remimazolam compared with propofol: a multicentre randomised controlled trial - Fechner, Jörg; El-Boghdadly, K.; Spahn, Donat Rudolf; Motsch, Johann; Struys, M.M.R.F.; Duranteau, O.; Ganter, M.T.; Richter, T.; Hollmann, M.W.; Rossaint, Rolf; Bercker, Sven; Rex, Steffen; et al. (Anaesthesia, 2024)
Remimazolam, a short-acting benzodiazepine, may be used for induction and maintenance of total intravenous anaesthesia, but its role in the management of patients with multiple comorbidities remains unclear. In this phase 3 randomised controlled trial, we compared the anaesthetic efficacy and the incidence of postinduction hypotension during total intravenous anaesthesia with remimazolam vs. propofol. A total of 365 patients (ASA physical status 3 or 4) scheduled for elective surgery were assigned randomly to receive total intravenous anaesthesia with remimazolam (n = 270) or propofol (n = 95). Primary outcome was anaesthetic effect, quantified as the percentage of time with Narcotrend® Index values ≤ 60, during surgery (skin incision to last skin suture), with a non-inferiority margin of -10%. Secondary outcome was the incidence of postinduction hypotensive events. Mean (SD) percentage of time with Narcotrend Index values ≤ 60 during surgery across all patients receiving remimazolam (93% (20.7)) was non-inferior to propofol (99% (4.2)), mean difference (97.5%CI) -6.28% (-8.89-infinite); p = 0.003. Mean (SD) number of postinduction hypotension events was 62 (38.1) and 71 (41.1) for patients allocated to the remimazolam and propofol groups, respectively; p = 0.015. Noradrenaline administration events (requirement for a bolus and/or infusion) were also lower in patients allocated to remimazolam compared with propofol (14 (13.5) vs. 20 (14.6), respectively; p < 0.001). In conclusion, in patients who were ASA physical status 3 or 4, the anaesthetic effect of remimazolam was non-inferior to propofol.
Gesehen am 26.03.2024